Analisis Sosiologi Sastra dalam Novel Bekisar Merah Karya Ahmad Tohari - Anastasia Yunianti; Namang, Katharina Woli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to clearly describe the main character's character education contained in the Novel Cantik Itu Luka by Eka Kurniawan. The main reason the researcher chose the title of this research is to provide an overview to the reading public that novels are not only a medium of entertainment for readers, but furthermore, novels have an important role in instilling the value of character education for novel connoisseurs in general. This study used the descriptive-qualitative method. The data collection technique used by the authors in this study was the reading and note-taking technique. Data analysis techniques used in this research are data reduction techniques and data presentation. The results showed that there were 7 types of character education values, including the values of responsibility, religious values, social care values, independent values, never giving up, romantic characters, and friendly and communicative.